2016
DOI: 10.1111/jan.13076
|View full text |Cite|
|
Sign up to set email alerts
|

Change in quality of life in older people with dementia participating in Paro‐activity: a cluster‐randomized controlled trial

Abstract: Pleasant and engaging activities facilitated by nursing staff, such as group activity with Paro, could improve quality of life in people with severe dementia. The trial is in adherence with the CONSORT statement and is registered at www.clinicaltrials.gov (study ID number: NCT01998490) [corrected].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(194 citation statements)
references
References 85 publications
7
181
0
6
Order By: Relevance
“…Although no previous study of the Sonas programme has measured the effect by stratifying on cognitive function, the findings from our study are consistent with a previous study [36] where they measured the effect of robot-assisted activity on quality of life, reporting a significant effect among people with severe dementia.…”
Section: Discussionsupporting
confidence: 91%
“…Although no previous study of the Sonas programme has measured the effect by stratifying on cognitive function, the findings from our study are consistent with a previous study [36] where they measured the effect of robot-assisted activity on quality of life, reporting a significant effect among people with severe dementia.…”
Section: Discussionsupporting
confidence: 91%
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included articles are summarized in Table 2. Of the 14 studies, six used a quasi-experimental design with one group pre-/post-test or post-test only design [48][49][50][51][52][53], two used retrospective exploratory design [54,55], two used randomize control trial (RCT) [56,57], one used cluster RCT [58,59], one used mixed-method design [14], one used qualitative design [60], and one used cross-sectional design [61]. Most of the studies were conducted in the United States (n= 7), followed by two in Australia, and one each in South Korea, Taiwan, Israel, Norway, and Spain.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three studies discussed a companion pet robot with the appearance of baby harp seal [58,59,63]. Of them, two RCTs demonstrated the effectiveness of animal-assisted therapy using the robot on maintaining quality of life [59,63] and decreasing symptoms of depression [58] and agitation [58] among older adults with moderate to severe dementia. One study qualitatively evaluating the robot from therapists' perspectives showed a positive attitude toward offering animal-assisted therapy when used by nurses in their practice [60].…”
Section: Robots With Aimentioning
confidence: 99%